Organised Retail in India: A Case Study of Bal-wart - Sahoo, Debajani; Mishra, Hari Govind (Indian Journal of Marketing, 2008)
Rising incomes and changing customer preferences have translated into a booming US$ 1 trillion emerging retail market in India. To sustain its high growth rates, global retail giant Wal-Mart is considering foraying into the Indian retail market. Wal-Mart has to contend with varied operational environment challenges such as Government FDI regulations, strict tenant laws, complexity of taxes, and challenges of red tape. Wal-Mart should take advantage of changing retail buying patterns and influences in the Indian consumer (consumption oriented, increasingly younger population) and the evolution of Indian retail industry from entertainment and convenience to wholesome shopping experience and efficiency. Wal-Mart must enter with locally customized supermarkets instead of the standard Western model to provide the right combination of goods important to the local populace. While it does so in the Indian market, it has to take into account the present competitors in the retail space. The various retail chains in the categories of hypermarket, supermarket, departmental stores, specialty chains, single and multi-brand outlets and the mom & pop stores are either direct or indirect competitors for Wal-Mart. A better strategy would be to partner with an existing Indian retail house for easier entry. Besides given the largely untapped potential of the retail market in smaller cities and towns, and given the cheap and quality goods Wal-Mart provides across the world, it can service this segment much better than existing customers. But now question arise can the Wal-Mart better serve the Indian consumer by fulfilling their need to the fullextent. By tieing up with Bharati could it build the best image in consumer mind&in the coming few years who will be the market leader (Reliance or Bal-Mart or somebody else).